2018
DOI: 10.1016/j.ophtha.2017.12.038
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone Inserts in Noninfectious Uveitis

Abstract: The repeated longer-term administration of DEX inserts in noninfectious uveitis patients, either alone or in combination with other therapies, led to improved CRT, BCVA, and VH. Underlying diseases and concomitant systemic therapy seem to have an impact on overall treatment benefit. Ocular complications were reversible and were managed by local treatment, with exception of cataract formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
21
0
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 37 publications
3
21
0
3
Order By: Relevance
“…In this study multiple injections yielded comparable visual and anatomical outcomes to single injections, and mean IOP did not change significantly during follow-up [46]. The efficacy and safety of repeated DEX implants in patients with NIUs were further confirmed by several studies, with a median duration of therapeutic effect of 6 months and a transient rise in mean IOP always well managed by topical medication [46][47][48][49].…”
Section: Evidence Of the Efficacy Of Dex In Posterior Non-infectious supporting
confidence: 67%
“…In this study multiple injections yielded comparable visual and anatomical outcomes to single injections, and mean IOP did not change significantly during follow-up [46]. The efficacy and safety of repeated DEX implants in patients with NIUs were further confirmed by several studies, with a median duration of therapeutic effect of 6 months and a transient rise in mean IOP always well managed by topical medication [46][47][48][49].…”
Section: Evidence Of the Efficacy Of Dex In Posterior Non-infectious supporting
confidence: 67%
“…A further prospective, interventional study confirmed the effectiveness of dexamethasone implants, either alone or in combination with systemic therapies, by improving bestcorrected visual acuity, central retinal thickness, and vitreous haze, especially in patients with idiopathic and sarcoid uveitis. 113 Systemic CS should be used similarly as in noninfectious uveitis (►Fig. 6).…”
Section: Corticosteroidsmentioning
confidence: 99%
“…More recently, it has also been approved for the treatment of diabetic macular edema (DME). Numerous studies examining various numbers of DEX treatments and lengths of treatment have demonstrated its effectiveness at treating RVO, 1-5 uveitis [6][7][8][9][10] and DME. [11][12][13][14][15][16] As patients receive multiple DEX implants over extended lengths of treatment the concern grows for more significant intraocular pressure (IOP) elevations and cataract progression, both well-documented complications.…”
Section: Introductionmentioning
confidence: 99%